1975
DOI: 10.1002/kin.550070204
|View full text |Cite
|
Sign up to set email alerts
|

Excited state kinetics of the π*←n photochemistry of hexafluoroacetone

Abstract: Abstract'The T * t n excited state kinetics of hexafluoroacetone are reinvestigated in the presence of a vibrational relaxer and sufficient triplet state quencher so that only the reactions of the electronically excited upper singlet state are examined. From a Stern-Volmer type analysis it is concluded that vibrational relaxation of the initially formed vibrationally and e)ectronically excited upper singlet state is via a multistage collisional mechanism. An activation energy of about 6 kcal/mole is reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…4 The relative positions and uncertainties in these energy levels are shown in Figure 10. The redistribution of internal energy in the excited triplet state can be due to intra-or intermolecular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The relative positions and uncertainties in these energy levels are shown in Figure 10. The redistribution of internal energy in the excited triplet state can be due to intra-or intermolecular processes.…”
Section: Discussionmentioning
confidence: 99%
“…This energy can be compared to the activation energy for loss of phosphorescence13 measured by other workers and the estimate of the "singlet state" activation energy. 4 The relative positions and uncertainties in these energy levels are shown in with AEST, the singlet-triplet energy gap (8 kcal mof1 < EST < 9 kcal mof1, ref 13), to derive the energy of the vibrationless triplet state, ET(00). AEt is the activation energy for toss of phosphorescence (15.5 kcal mor1, ref 13) and AES is the estimated singlet state activation energy (6 kcal moP1, ref 3).…”
Section: Discussionmentioning
confidence: 99%
“…The pentadienyl radical precursor was synthesized by the sequence of reactions indicated in Scheme II. The perester was obtained as a white solid, mp 34- 35 Ir (cm film) 6a 6.4-6.8 (1 H, br d, J = 10 Hz, 273 3030, 1640, Hb), 5.4-6.0 (3 H, m, Ha's), (17 781) 1615,915, 1.2-2.4 (14 H, m) 265 870 (17 380) 6b 5.9-6.2 (1 H, br d, J = 10 Hz, 273 3030, 1635, Hb), 5.4-5.9 (3 H, m, Ha's), (23 934) 1605, 915, 2. 35-2.65 (2 H, br t, 7 = 6 Hz), 265 875…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that reaction [-61, the reverse of [6], is not an important decomposition-route for this radical. Later, Gile and Whittle (16) studied the photolysis of a mixture of CF,COCF, and CH,COCH,, and observed the fornlation of CF,COCH,.…”
Section: Mec/zc~nist~z For Prod~tct Formntiolzmentioning
confidence: 99%
“…In some earlier work related to the formation and decomposition OF (CF,),(CH,)-CO as shown in [6] and [7], Smith and Calvert (IS) formed the same radical through reaction [lo]…”
Section: Mec/zc~nist~z For Prod~tct Formntiolzmentioning
confidence: 99%